1997
DOI: 10.1104/pp.113.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Endo-β-Mannanase Activity Present in Cell Wall Extracts of Lettuce Endosperm prior to Radicle Emergence

Abstract: Lettuce (Lactuca safiva 1.) endosperm cell walls isolated prior to radicle emergence underwent autohydrolysis, the rate of which was correlated with whether radicle emergence would subsequently occur. Extraction of endosperm cell walls with 6 M LiCl suppressed autohydrolysis, and the desalted extract possessed activity that was capable of hydrolyzing purified locust bean galactomannan but not arabinogalactan, carboxymethylcellulose, glucomannan, polygalacturonic acid, tomato galactomannan, or native lettuce en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 16 publications
0
26
1
Order By: Relevance
“…These authors found that, even though there was an increase in β-mannanase activity in the seeds before the projection of the rootlet, the reduction in water potential either delayed or prevented the emergence of the rootlet. Dutta et al (1997) reported that this enzyme is expressed before germination, and it is regulated by the same conditions that control germination. Consequently, enzyme activity decreases with increases in seed germination rates.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that, even though there was an increase in β-mannanase activity in the seeds before the projection of the rootlet, the reduction in water potential either delayed or prevented the emergence of the rootlet. Dutta et al (1997) reported that this enzyme is expressed before germination, and it is regulated by the same conditions that control germination. Consequently, enzyme activity decreases with increases in seed germination rates.…”
Section: Discussionmentioning
confidence: 99%
“…Endo-β-mannanase was involved in weakening of the lettuce endosperm cell walls at high temperatures (Dutta et al, 1997). Therefore, endo-β-mannanase activity was assayed during seed germination at 35°C (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…They did not isolate or identify the enzyme. Dutta et al (1997) reported that a cell-wall-bound endo-β-mannanase was expressed in lettuce seed endosperm prior to radicle protrusion and was regulated by the same conditions that govern seed germination. These authors suggested that endo-β-mannanase was involved in weakening of the lettuce endosperm cell walls.…”
Section: Introductionmentioning
confidence: 99%
“…The latter experiment included only a single time point at 72 h of imbibition; therefore, it is possible that by that time mannanase activity had already declined below the sensitivity of the assay used. On the other hand, ABA inhibits development of mannanase synthesis or activity in lettuce (Dulson et al, 1988;Dutta et al, 1996) and fenugreek (Trigonella foenum-graecum L.; Malek and Bewley, 1991) endosperm. Groot and Karssen (1992) showed that ABA inhibits mechanical weakening of the tomato endosperm cap, but we found no inhibition of mannanase activity at a time when seeds that were allowed to imbibe in water would have completed radicle emergence.…”
Section: T5 Seeds Cerminating At Reduced +mentioning
confidence: 99%